Relationships between Defects of Related Ability and Joint Attention of Children with Autism - Yumei CHEN; Zhenping LIN; Hong WANG; Jiewen CHEN; Weixin HUANG (康复学报)
The defects of related ability of children with autism are closely related to their joint attention. This research rearranged and analyzed the findings related to joint attention of autism children at home and abroad in recent years, and summarized the effects of defects of joint attention on related ability, including language communication, cognition, social communication, imitation, games, emotions, etc., then analyzed their relationships, so as to provide some theoretical basis for the treatment of joint attention of autism children.